Progress and Opportunities of Doubled Haploid Production - Asif, Muhammad; SpringerLink (Online service) (Heidelberg : Springer International Publishing : Imprint: Springer, 2013)
Deals with the historical perspectives and the current status of doubled haploid production along with its practical implications in basic and applied research. It highlights various haploid production methods with a comprehensive discussion on their pros and cons, bottlenecks, and embryogenic pathways. The review also describes in detail the results of molecular and genomic studies conducted to investigate the underlying principles of this spectacular technique that has changed the status of many species from recalcitrant to responsive over the last ninety years.
Abstract -- Introduction/Historical background -- Haploid Production -- Androgenesis -- Microspore culture -- Donor plant$1 (Bs growth and developmental conditions -- Collection of floral organs -- Pretreatments -- Microspore$1 (Bs isolation and purification -- Media Composition -- Regeneration -- Increase in Ploidy Level -- Albinism -- Pathways of microspore embryogenesis -- Anther Culture -- Genotype, physiological state, growth and developmental stage of donor plants -- Pretreatments and media composition -- Uniparental Chromosome Removal/Elimination or Wide Hybridization -- Bulbosum Method -- Haploids using maize as a pollen donor -- Haploids using Solanum phureja and maize inducer lines -- Gynogenesis -- Genotype -- Developmental stage of female gametophyte -- Pretreatment -- Composition of media -- Parthenogenesis -- Applications and uses of haploids -- Homozygosity -- Genomics -- Mutation -- Transformation -- Synthetic or Artificial Seed Production -- Future Thrust -- Conclusion -- References.s
Keywords: Life sciences; Plant breeding; Life Sciences; Plant Breeding/Biotechnology.; Plant Genetics & Genomics